Analisysis of student satisfaction on lecturers performance in Management Study Program Terbuka University - Rustandi, Dodi; Kusnadi, Engkus; Suntoro, Suntoro; Suwardi, Suwardi; Mawan, Mawan (Trigin Publisher, 2024)
The development of higher education today is extremely rapid, moreover the need for education is utgently needed by student, so it is obligatory for all tertiary institutions to really pay attention to the quality of lecturers who will provide maximum service to student. In this study , what kind of lectururers who will provide maximum service to student. In this study, what kind of lecturer performance has an impact on the level of student satisfaction in the Management Study Program at Terbuka University. This research is classified as a quantitative type, so trhe discussion carried out is data obtained from research which is the result of SPSS 25.0 analysis, observations, interviews, and questionnaires. The type of sample used is purposive sampling. From the research, the results were obtained, namely based on SPSS 25.0 data, we can conclude of management lectures with the highest score, namely Tangible 64.4% and Responsiveness 35.6%.